Features of iNOS activity in the skin lesions of patients with psoriasis and concomitant hypertension - G.І. Makurina; M.М. Baudarbekova (Patologìâ)
Objective: To identify the features of the activity of nitric oxide synthase by immunohistochemical study of skin samples in patients with psoriasis and concomitant hypertension.